PRIMARY DENTAL PREVENTION OF CHILDREN'S POPULATION IN TECHNOGENIC REGION - E.N. Dychko; A.V. Schtompel; P.L. Sribnik (Український стоматологічний альманах)
High incidence of basic dental disease poses the problem of their treatment and prevention in a number of the most important in the practice of dentistry. If the secondary and tertiary dental prophylaxis has a frank success, the primary is in the process of development and improvement. Therefore, to talk about the successes in the national preventive dentistry, particularly in the child population, it is not necessary they are quite modest. At the same time, the countries of Europe and North America have achieved significant results in the prevention of major dental diseases, thus reducing the prevalence and intensity of dental caries and periodontal inflammation to impressive numbers. A whole set of adverse conditions, including financial, organizational and cultural nature does not allow to achieve tangible results in the national preventive dentistry. However, scientific dentistry has sufficient expertise in the nature of the origin and formation of teeth and periodontal disease, to achieve convincing successes in preventive dentistry. However, there are features of the etiology and pathogenesis of diseases in different living conditions of specific populations of people that need to learn.